ANALISIS KEMAMPUAN NUMERASI PESERTA DIDIK PADA SOAL MATEMATIKA SD NEGERI SONGGOM 03 - Nurul Desy Fitria Rahman (JS (JURNAL SEKOLAH), 2022)
Abstract: Analysis of Students' Numerical Ability in Mathematics Problems at SD Negeri Songgom 03. The formulation of the problem in this study is: How is the numeracy ability of students in mathematics at SD Negeri Songgom 03. The purpose of this study is to determine the numeracy abilities of students in math problems. Data collection techniques in this research is to use interview techniques, observation and documentation. This research method uses a qualitative descriptive method. The object in this study is primary data, namely data directly obtained by the resource persons, namely grade 1 students, grade 1 teachers, and parents. The results of research on students' numeracy skills in mathematics, namely there is numeracy ability, namely students are able to solve math-related problems by themselves without the help of others, students' abilities are able to solve math-related problems that still require teacher assistance, low numeracy skills, namely students are still weak in counting so they always need the help of the teacher. Thus, it can be said that the ability to count in mathematics there are 3 categories, namely high, medium and low. Keyword : Numeracy Skills, Mathematics Abstrak : Analisis Kemampuan Numerasi Peserta Didik Pada Soal Matematika SD Negeri Songgom 03. Rumusan masalah pada penelitian ini yaitu: Bagaimana kemampuan numerasi peserta didik pada soal matematika di SD Negeri Songgom 03. Tujuan penelitian ini adalah untuk mengetahui kemampuan numerasi peserta didik pada soal matematika. Teknik pengumpulan data dalam penelitian ini adalah dengan menggunakan teknik wawancara, observasi dan dokumentasi. Metode penelitian ini menggunakan metode deskriptif kualitatif. Objek dalam penelitian ini adalah data primer yaitu data yang langsung diperoleh oleh narasumber yaitu peserta didik kelas 1, guru kelas 1, dang orang tua. Hasil penelitian pada kemampuan numerasi peserta didik pada soal matematika yaitu terdapat kemampuan numerasi tinggi yaitu peserta didik mampu memecahkan masalah terkait pada soal matematika dengan sendirinya tanpa bantuan orang lain, kemampuan numerasi sedang yaitu peserta didik mampu menyelesaikan masalah terkait pada soal matematika yang masih memerlukan bantuan guru, kemampuan numerasi rendah yaitu peserta didik masih lemah dalam berhitung sehingga selalu memerlukan bantuan guru. Dengan demikian dapat disimpulkan bahwa kemampuan numerasi pada soal matematika terdapat 3 kategori yaitu tinggi, sedang dan rendah. Sedanglan Kata Kunci : Kemampuan Numerasi, Matematika